Temperate and boreal rainforests of the world ecology and conservation - DellaSala, Dominick A. (Island Press, 2011)
In the first book of Its Kind, DellaSala brings together leading scientists from around the world to describe the ecology and conservation of temperate and boreal rainforests, unique ecosystems that are largely overlooked but rich in plants and wildlife and containing some of the most massive trees on Earth. Temperate and Boreal Rainforests of the World offers a global vision rooted in ecological science for all who are concerned about the plight of these remarkable forests.